Synthesis and cytotoxic evaluation of some quinazolinone- 5-(4-chlorophenyl) 1, 3, 4-oxadiazole conjugates - Farshid Hassanzadeh; Hojjat Sadeghi-Aliabadi; Elham Jafari; Azadeh Sharifzadeh; Nasim Dana (Wolters Kluwer Medknow Publications, 2019)
1, 3, 4- Oxadiazoles and quinazolinones are privileged structures with extensive biological activities. On account of reported anticancer activity of them, in this study, a multi-step reaction procedure has been developed for the synthesis of some quinazolinone-1, 3, 4-oxadiazole derivatives. Reaction of the synthesized 3-amino-4(3H) quinazolinone derivatives with chloroacetyl chloride in the presence of dichloromethane/triethylamine yielded 2-chloro -N-(4-oxo-2-quinazolin3 (3H)-yl) acetamide derivatives as intermediate. Treatment of the resultants with 5- (4-chlorophenyl) 1, 3, 4-oxadiazole-2-thiol in dry acetone and potassium carbonate gave coupled derivatives of quinazolinone-1, 3, 4-oxadiazole. The cytotoxic effect of final compounds was tested against MCF-7 and HeLa cell lines using MTT assay. Compound 2-(5-(4-chlorophenyl)-1,3,4-oxadiazol-2-ylthio) N-(4-oxo-2-propylquinazolin)3(4H)acatamide 6a exhibited remarkable cytotoxic activity at 10 and 100 μM against HeLa cell line. The alteration of substituents on C2 of quinazolinone ring revealed that the introduction of propyl moeity improved cytotoxic activity against HeLa cell line.